Houses of Worship Development Management in Pluralistic Cities: Comparative Study of Manado and Gorontalo - Radlyah Hasan Jan; Fitria Ayu Lestari Niu; Youlanda Hasan (UIN Sunan Gunung Djati, 2025)
This study examines the dynamics of worship house construction management—specifically mosques and churches—within the pluralistic urban contexts of Manado and Gorontalo. The objective of this research is to analyze how religious pluralism and social capital influence the management process through the POES framework (Planning, Organizing, Evaluation, and Supervision). Employing a descriptive qualitative approach with a comparative case study design, data were collected through in-depth interviews, participatory observation, and documentation involving religious leaders, local government representatives, and community organizations. Data analysis was conducted in three stages: data reduction, thematic coding, and narrative interpretation. The findings indicate that although Manado (predominantly Christian) and Gorontalo (predominantly Muslim) possess distinct demographic structures, both display similar management patterns—participatory, transparent, and rooted in social trust. During the planning and funding stages, construction initiatives originated from community-driven efforts based on collective self-help (gotong royong), supported symbolically by government and religious institutions. In the organizing stage, the committee structure was non-hierarchical and inclusive, involving women, youth, and interfaith participants, thereby strengthening social solidarity. In the evaluation and supervision stages, a community-based moral accountability mechanism was applied, where financial transparency and public participation served as key instruments of project control. However, the study also reveals potential dysfunctions, including dependence on charismatic figures and the absence of professional auditing systems, which could hinder project sustainability if not balanced with institutional capacity building. These findings confirm that, in pluralistic societies, the success of worship house management is not solely determined by technical procedures such as the Project Management Body of Knowledge (PMBOK), but also by local cultural norms—such as musyawarah (deliberation), gotong royong (mutual cooperation), and interfaith tolerance—which serve as sources of social capital and moral legitimacy. Theoretically, this research contributes by integrating the POES management model with social capital theory in religious contexts. Practically, it provides policy recommendations for governments and religious institutions to strengthen worship house governance through community-based management training, interfaith monitoring mechanisms, and inclusive, equitable development policies.